Joint Prevalence of Sitting Time and Leisure-Time Physical Activity Among US Adults, 2015-2016 - Ussery, Emily N. (JAMA, 2018)
This study uses 2015-2016 National Health and Nutrition Examination Survey data to assess prevalence of daily sitting time and weekly leisure-time physical activity among US adults.